Efektifitas Penerapan Pembimbingan Kelompok Dalam Upaya Meningkatkan Kompetensi Guru Rayon SMP Negeri Ekoae Dalam Penyusunan Proposal PTK - Anselmus Doa Gembo (Program Studi Pendidikan Ekonomi, Universitas Flores, 2021)
preparing CAR proposals that are useful for teachers in increasing teacher professionalism This study aims to determine the extent to which the effectiveness of the application of group guidance in an effort to improve the competence of district teachers of SMP Negeri Ekoae in in daily tasks. This School Action Research (PTS) consists of two cycles, where in each cycle there are four stages, namely planning, implementation, observation and reflection. The success indicator in this study is the Competence of the District Teachers of SMP Negeri Ekoae: if > 10% of the total coaching participants have obtained an average score of 85.00. The results of the School Action Research (PTS) in cycle II obtained the following data; 1) supervisor observation (4.22), 2) teacher observation (4.14), 3) classical work results (84.02). The success indicator has been exceeded. The School Action Research (PTS) was declared successful, and the research was stopped in cycle II. Group guidance was very effective in improving the competence of the district teachers of SMP Negeri Ekoae in preparing CAR proposals because 90 percent of the total participants were 35 (thirty five) teachers have succeeded in compiling CAR proposals as expected. It is recommended that peer school principals carry out mentoring activities for teachers who are their responsibility in an effort to increase competence in sustainable professional development activities (PKB).